2009
DOI: 10.3201/eid1508.081642
|View full text |Cite
|
Sign up to set email alerts
|

Slave Trade and Hepatitis B Virus Genotypes and Subgenotypes in Haiti and Africa

Abstract: TOC Summary: The spread of genotype E in Africa occurred after the end of the transatlantic slave trade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

26
105
5
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(137 citation statements)
references
References 27 publications
26
105
5
1
Order By: Relevance
“…HBV/A was by far the most common (79.1 %), with most cases belonging to the 'African-Asian' HBV/A1 subgenotype (68.6 %) and the remaining 10.5 % to the 'European' HBV/A2. Such results have also been described in other countries with a history of African slave trade (Andernach et al, 2009;Santos et al, 2010), but the proportion of HBV/A1 was significantly higher in our study: 68.6 % in Martinique vs 43 % and 37 % in Haiti and Brazil, respectively (P,0.001).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…HBV/A was by far the most common (79.1 %), with most cases belonging to the 'African-Asian' HBV/A1 subgenotype (68.6 %) and the remaining 10.5 % to the 'European' HBV/A2. Such results have also been described in other countries with a history of African slave trade (Andernach et al, 2009;Santos et al, 2010), but the proportion of HBV/A1 was significantly higher in our study: 68.6 % in Martinique vs 43 % and 37 % in Haiti and Brazil, respectively (P,0.001).…”
Section: Discussionsupporting
confidence: 90%
“…More partial HBV/D4 sequences have also been described (Andernach et al, 2009, Norder et al, 2004, Osiowy et al, 2011, Santos et al, 2010 mainly in the S gene. Phylogenetic analyses with all published D4 partial sequences confirmed that Martinican strains clearly belong to the HBV/D4 subgenotype but do not form a separate cluster (data not shown).…”
mentioning
confidence: 96%
“…A recent phylogenetic study suggests that West African hepatitis B virus (HBV) lineages were introduced to Haiti during the peak years of slave movement (1). Similarly, recent studies of human T-cell leukemia virus type 1 (HTLV-1), which sometimes combine human and viral evidence, have indicated that Surinamese, Guyanan, Brazilian, Argentinian, and Peruvian HTLV-1 lineages grouped among West African lineages (3,12,32).…”
Section: Discussionmentioning
confidence: 99%
“…However, a close coevolution of HDV-1 and HBV-E seems unlikely, since HDV-1 can be found worldwide, whereas HBV-E is largely confined to Africa and is thought to have a short evolutionary history (8,44,45). Moreover, several lines of evidence suggest that HBV-E was only recently introduced into the African population (8,44,45).…”
Section: Discussionmentioning
confidence: 99%